2003
DOI: 10.1103/physrevd.67.035009
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and studying Higgs bosons at a photon-photon collider

Abstract: We examine the potential for detecting and studying Higgs bosons at a photon-photon collider facility associated with a future linear collider. Our study incorporates realistic γγ luminosity spectra based on the most probable available laser technology. Results include detector simulations. We study the cases

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 30 publications
0
97
0
Order By: Relevance
“…6 In order to gain confidence in our method we checked our procedure on the one-loop expansions, Eqs. (7,8), and compared with the exact results, Eqs. (4,5).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In order to gain confidence in our method we checked our procedure on the one-loop expansions, Eqs. (7,8), and compared with the exact results, Eqs. (4,5).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…While none of the above measurements alone can provide information on the partial width (what is measured is σ(pp → H)· Br(H → γγ)), their combination with signals in other decay modes, will allow a determination of the total width of the Higgs and of the couplings with a precision of 10-40% [5]. A much better determination of the Higgs width into two photons could be achieved at a e + e − linear collider, via the fusion process γγ → H, with the photons generated by Compton-back scattering of laser light [6,7]. In this case, it has been shown that σ(γγ → H)· Br(H → bb) could be measured to a precision of a few percents [8], providing an almost direct determination of the width of H → γγ (the Br(H → bb) is large for intermediate Higgs masses and therefore quite insensitive to the total width).…”
Section: Introductionmentioning
confidence: 99%
“…A future linear collider will be able to see and carefully study a Higgs with mass m h < ∼ √ s − m Z in e + e − mode, and perhaps slightly higher in γγ mode [38,39,40]. Indications of SU(3) electroweak unification could also come from direct collider probes and precision electroweak studies that match expectations [41] of minimal models and beyond.…”
Section: B the Next-to-minimal Supersymmetric Standard Modelmentioning
confidence: 99%
“…There are several design proposals for a collider with such capabilities, such as a linear/circular e þ e − machine [20,21], muon-collider [22,23], or γγ machine [24,25]. Although the proposed physics programs are different in each case, the common goal is to achieve Oð%Þ level precision on the measurement of Higgs couplings.…”
Section: Introductionmentioning
confidence: 99%